PROGNOSIS OF FEATURES OF COURSE OF TYPE 2 DIABETES MELLITUS IN PATIENTS WITH NON-PSYCHOTIC MENTAL DISORDERS - N. P. Garganeyeva; M. F. Belokrylova (Бюллетень сибирской медицины)
The logistic regression method is justified prognostic importance of psychosocial factors, along with other factors (predictors), determining the formation of psychosomatic relations and peculiarities of the course of type 2 diabetes mellitus in 203 patients with neurotic, affective and organic non-psychotic disorders, to develop a comprehensive programme for secondary prevention and rehabilitation. Group of high risk of development of DM is constituted by patients with experience of psychosocial stress, whose heightened level of glycaemia is associated with depressive and anxiety disorders.